Depiction of a Dhvaja Vahaka (flag bearer) - Temples of India Project Team (Jio Institute, 2024)
One of the most interesting sculptures is of a dhvaja vahaka (flag bearer), placed at the shikhara (superstructure) of the garbhagriha (sanctum sanctorum). The bearded male figure is shown standing, facing the shikhara, with one leg placed on the floor and the other placed on a lotus pedestal. He is wearing a crown and is heavily adorned with jewels. He is carrying a sword which can be seen hanging from his waist. His hands are shown one above the other, holding a hollow circular disk, which must have been used to hold the dhvaja (flag) of the temple.